Implementation of a decision support system for selecting palm oil processing waste disposal location in Pagar Merbau using the topsis method - Nikpani, Karen; Syahputra, Siswan; Br.Sitepu, Kristina Annatasia (Journal of Engineering, Technology and Computing (JETCom), 2025)
The management of palm oil solid waste, particularly Empty Fruit Bunches (EFB), remains a major challenge in the palm oil industry due to its potential to cause environmental pollution if not properly handled. One solution to this problem is selecting appropriate disposal sites by considering various technical, environmental, and social criteria. This study aims to implement a Decision Support System (DSS) using the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method for selecting palm oil waste disposal locations in Pagar Merbau. The criteria applied include land area, number of trees, soil type, plant age, nutrient requirements, and soil fertility. The system was developed using PHP and MySQL, and tested with the blackbox testing method. The results show that the system effectively supports decision-making by ranking alternative sites based on their highest preference values. Therefore, the implementation of a TOPSIS-based DSS proves to be effective in determining the most optimal location for palm oil waste disposal.